Docker containers (LiveLessons., 2017)
"With cloud computing, applications need to move around efficiently and run almost anywhere. In this video, learn how you can create containerized applications with Docker that are light-weight and portable. First, Chris shows you how to begin using Docker on Ubuntu, Red Hat Enterprise Linux, or Fedora systems (with options of Windows or Mac OS X). Then he shows how to pull and push Docker container images from and to Docker registries. The next few lessons get you started running and investigating how containers work. After that, the video shows you how to build your own Docker images. The video then touches on orchestration tools such as Kubernetes and GearD for deploying containers. And finally, it provides some tips for developing your own Docker containers."--Resource description page